2005
DOI: 10.1143/jjap.44.3712
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Field-Effect Transistors Based on Organic Selenium-Containing Semiconductor

Abstract: We report on the fabrication and characterization of single crystal field-effect transistors (FETs) based on 2,6-diphenylbenzo[1,2-b:4,5-b']diselenophene (DPh-BDSe). These organic field-effect transistors (OFETs) function as p-channel accumulation-mode devices. At room temperature, for the best devices, the threshold voltage is less than -7V and charge carrier mobility is nearly gate bias independent, ranging from 1cm 2 /Vs to 1.5 cm 2 /Vs depending on the source-drain bias. Mobility is increased slightly by c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…On/off ratios in this and most of the other single crystal device systems routinely exceed 10,000. Representative data from our own single crystal studies are shown in Table 1 [76,89,104,105], while images of selected organic semiconducting crystals are displayed in Figure 3. Except for the case of rubrene for which Podzorov [83,95] It is worth noting that the mobility of copper phthalocyanine,dichlorotetracene, and the selenium substituted compounds are at least one order of magnitude larger in single crystal form than in thin films.…”
Section: Molecular Crystals and Devicesmentioning
confidence: 99%
“…On/off ratios in this and most of the other single crystal device systems routinely exceed 10,000. Representative data from our own single crystal studies are shown in Table 1 [76,89,104,105], while images of selected organic semiconducting crystals are displayed in Figure 3. Except for the case of rubrene for which Podzorov [83,95] It is worth noting that the mobility of copper phthalocyanine,dichlorotetracene, and the selenium substituted compounds are at least one order of magnitude larger in single crystal form than in thin films.…”
Section: Molecular Crystals and Devicesmentioning
confidence: 99%
“…Organic field-effect transistors (OFETs) have attracted much attention as low-cost alternatives to conventional silicon-based transistors, and recent intensive research efforts in this field have led to the development of a number of superior p -channel organic semiconductors showing mobilities higher than 0.1 cm 2 V -1 s -1 in FET devices, almost comparable to that of amorphous silicon. Showing remarkable properties are pentacene as the best thin-film material (0.3−0.7 cm 2 V -1 s -1 on a Si/SiO 2 substrate, 1.5 cm 2 V -1 s -1 on a chemically modified Si/SiO 2 substrate, and 3.0 cm 2 V -1 s -1 on a modified alumina substrate 4 ) and rubrene as the best single-crystal material (∼20 cm 2 V -1 s -1 ) . One of the remaining key challenges in the practical application of such OFETs is to enhance device durability.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray crystal structural analysis was performed using a Rigaku RAXIS RAPID imaging plate area detector with graphite monochromated Cu-K ( = 1.5418 Å) radiation at -100 °C. Top-contact type single crystal OFET devices were prepared using a crystal lamination process [13,14]. We used an n + -doped Si wafer with a 220 nm thick thermally grown SiO 2 layer, as a substrate for the lamination process, and this was treated with a thin film (ca.…”
Section: Methodsmentioning
confidence: 99%